An Assessment of Readiness To Online Teaching And Learning By Teachers In Institutions Of Higher Learning. A Case Study of a State University In Zimbabwe - Peter Bhibhi; Blessed Mveku; Newton Chinyamunjiko; Chosani Simon; Chalton.N.Nyakurimwa; Tanaka.T.T. Mutero (International Organization Of Scientific Research, 2023)
This research was conducted to assess teachers’ readiness to adopt the new model of online teaching and learning at a state university in Zimbabwe during and post covid-19 pandemic. This was prompted by the fact that most institutions of learning were forced to adopt online learning as a replacement to the traditional face- to-face classroom model in response to persistent lockdowns without assessing their readiness from various ways such as teachers’ and students’ readiness. The quantitative research approach was adopted and data was collected through structured and guided questionnaires. Descriptive and inferential statistics from SPSS were used for data analysis. The major findings are that teachers are prepared to shift from face-to-face mode of learning to online learning and they do possess skills required for conducting online lectures. Teachers are developing a positive attitude towards the new norm, but more training is needed particularly on advanced computer skills.